Air-side heat transfer and pressure drop characteristics of flat-type, U-and V-shaped microchannel condensers for refrigerator applications. (September 2021) - Oh, Sung Hyuk; Lee, Sang Hun; Lee, DongChan; Moon, Sung Hyun; Kim, Yongchan
Highlights: Heat transfer characteristics of microchannel condensers (MCHXs) are measured. The Colburn j-factor and friction factor of enhanced MCHXs are compared. Empirical correlations of the Colburn j-factor and friction factor are developed. A guideline to determine optimal designs of condensers in refrigerators is provided. Abstract: In this study, the air-side heat transfer characteristics of microchannel heat exchangers (MCHXs), with enhanced shapes as condensers in refrigerators, are investigated. The heat transfer performances of flat-type, U- and V-shaped MCHXs, and conventional spiral fin-tube heat exchangers were measured and compared at various air flow rates and inlet temperatures. Furthermore, the Colburn j -factor and friction factor of the MCHXs were analyzed as a function of the Reynolds number. The second-type volume and area goodness factors were also analyzed to compare the heat transfer performances of the MCHXs considering various design parameters. Additionally, the empirical correlations of the Colburn j -factor and friction factor for U- and V-shaped MCHXs were developed using dimensionless parameters that reflect geometric and operating conditions. Hence, a U-shaped MCHX with a longer tube length was recommended to obtain a high absolute heat transfer rate, while a flat-type MCHX was recommended to realize high compactness and heat transfer efficiency.